PENGARUH KINERJA LINGKUNGAN TERHADAP REAKSI INVESTOR MELALUI PENGUNGKAPAN SUSTAINABILITY REPORT - Nindha Utami Cahaya Muchti; Aristanti Widyaningsih (STIE Pelita Nusantara Semarang, 2014)
This research aims to find out how the influence of the environmental performance and the level of disclosure of Sustainability Report to investors in the period around the date of the publication of the report PROPER and Sustainability Report on the mining and manufacturing companies listed on the Indonesia Stock Exchange (IDX). In this study an indicator that is used to author the PROPER ranking of environmental performance, to measure Sustainability Report disclosure there is an indicator of economic performance, environmental performance and social performance. As for the indicators used to measure the reaction of investors represented by the Cumulative Abnormal Return. The methods used in this research is descriptive and verifikatif methods. The population of this research is a company manufacturing and mining were listed on the Indonesia Stock Exchange (IDX) in 2009-2010. Based on purposive sampling technique was then taken as many as 15 of the sample company. Statistical analysis used was multiple linear regression. The test results of the three hypotheses are: the first that environmental performance does not have a positive influence on investor reaction, the latter of which States that the disclosure of Sustainability Report has no effect on the reaction of investors was positive, and the third States that the environmental performance and Sustainability Report disclosure simultaneously have no effect on the reaction of investors on the company’s manufacturing and mining are registered on the IDX.